Comparative and collaborative studies for the validation of a nested PCR for the detection of Xanthomonas axonopodis pv. dieffenbachiae from Anthurium samples. (17th June 2013) - Chabirand, A.; Jouen, E.; Pruvost, O.; Chiroleu, F.; Hostachy, B.; Bergsma‐Vlami, M.; Bianchi, G.; Cozzolino, L.; Elphinstone, J.; Holeva, M.; Manole, F.; Martini, P.; et al.
<x xml:space="preserve">Abstract</x> Efficient control of Xanthomonas axonopodis pv. dieffenbachiae, the causal agent of anthurium bacterial blight, requires sensitive and reliable diagnostic tools. The European standard EN ISO 16140:2003 has been followed to compare a nested PCR assay (N‐PCR) to a reference method (isolation and serological identification of bacterial colonies) and to other alternative serological detection methods. The evaluation was performed in two steps: a comparative study and a collaborative study involving 15 European laboratories. Although inclusivity was maximal (100%) for all methods, a maximal exclusivity was obtained only with N‐PCR followed by an enzymatic restriction digestion of the amplicons. Exclusivity indices of 90·6, 88·7 and 47·2% were found for indirect ELISA, immunofluorescence and double antibody sandwich ELISA, respectively. An exclusivity of 92·5% was obtained with the reference method, further increased to 100% if pathogenicity tests were performed as a supplemental assay. The best level of sensitivity (relative detection level) was obtained with the reference method followed by the N‐PCR assay. The N‐PCR performance in terms of relative accuracy, accordance and concordance was very similar to that of the reference method. Moreover, N‐PCR had undeniable advantages compared to the reference method (less labour‐intensive and less time‐consuming). In addition, post‐test probabilities of infection were calculated to select the most appropriate detection scheme related to the prevalence of the pathogen. The N‐PCR assay has since been included in a revised version of the EPPO detection protocol.